PLEIADES-HR SYSTEM PRODUCTS PERFORMANCE AFTER IN-ORBIT COMMISSIONING PHASE - C. Panem; F. Bignalet-Cazalet; S. Baillarin (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2012)
Launched on 2011, December 16th by the second Soyuz operated in French Guiana, PLEIADES-HR acquired its first high resolution images 3 days after. The PLEIADES program is a space Earth Observation system led by the French Space Agency (CNES), it provides the first european high resolution satellite which will simultaneously acquire in Panchromatic and Multi- Spectral modes 20 km wide images with a 70 cm nadir resolution. Imaging capabilities have been highly optimized in order to acquire, in the same pass, along-track mosaics, stereo pairs and triplets, and multi-targets. Ground segment processes automatically data to ensure operational requirements and quick access to images for the users. Since ground processing capabilities have been taken into account very early in the mission development, it has been possible to relax some costly on-board components requirements, in order to achieve a cost effective on-board/ground compromise. Starting from the PLEIADES system and on board characteristics, this paper first presents an overview of ground segment functional breakdown. Then it focuses more precisely on the different levels of products and associated processing performances. Finally the paper shows how appropriate ground processing systems allowed CNES Image Quality team to assess radiometric and geometric performances during the 6 first months of PLEIADES 1A.